Improvement of Microbial Fuel Cell Electricity Generating with Bacterial Isolate Implementation on Electrode in Liquid Waste of Pindang Fish Processing improvement of Microbial Fuel Cell Electricity Generating with Bacterial Isolate Implementation on Electrode in Liquid Waste of Pindang Fish Processing - Bustami Ibrahim; Desniar; Rofi Muyassar (Journal of Clean Technology, 2026)
Abstract Microbial Fuel Cells (MFC) can generate electricity from organic substances which is converted to simply chemical component to discharge protons and electrons by microbial activity. Microbial Fuel Cell (MFC) is a technology that produces environmentally friendly energy because MFC in its use does not produce CO2 emissions.   Bacteria that is able to generate electricity grouped as exoelectrogen bacteria. Two kinds of bacteria has isolated from operating MFC with activated sludge need to find its performs which are Pediococcus acidilactici and Staphylococcus warneri. This study aims to determine the influence of sticking bacteria (Pediococcus acidilactici and Staphylococcus warneri) on electrode plates and the addition of activated sludge to increased electricity of MFC, reduce pollutant load from salt-boiled fish processing wastewater, and microbial density in electrode plates. This study has five stages, namely, bacterial cultivation, bacterial sticking on electrodes surface, activated sludge  acclimatization, MFC assembly, and electrical measurement. This study used four treatments namely, electrodes that bacteria do not attach with and without added activated sludge (KoL and Ko), electrodes attached with bacterial isolates (anodes with Pediococcus acidilactici and cathode with Staphylococcus warneri) with and without active sludge (AKL and AK). AKL treatment obtained the highest average electrity value with a voltage value of 0.31±0.02 V, an electric current value of 3.28±0.66 mA, and a power value of 1.15±0.25 mW. Pollutant loads in COD, BOD, and TAN parameters decreased by 57%, 38%, and 92%. The sticking bacteria on the electrodes surface with activated sludge added was able to increase the density of bacteria on the electrode plate.